Comparative study of fine-needle aspiration cytology and biopsy in diagnosis of lymphadenopathy in pediatric age group - Agarwalla, Sunil Kumar; Saji, Anjali (Indian Journal of Child Health, 2020)
Background: Excision biopsy and its histopathological examination have for many years been the final diagnostic procedure in diagnosis of lymphadenopathy. However, it is troublesome, expensive, and delays in treatment. Objective: The objective of the study was to find the association between fine-needle aspiration cytology (FNAC) and histopathology in diagnosing children with lymphadenopathy. Materials and Methods: This observational analytical cross-sectional study was conducted in the department of pediatrics of a teaching institution of Odisha, India. Fifty children attending our outpatient department and/or inpatient department for any cause, clinically diagnosed as local or general lymphadenopathy under 14 years of age were included in the study. Proportion of lymphadenopathies detected by FNAC, histopathology, and biopsy was calculated. We also calculate the proportion of lymphadenopathy detected by FNAC in three different types of scenarios, that is, definite diagnosis, diagnosis suspected and undiagnosed cases. Results: The median age was 7 years (2–14 years) and male-to-female ratio was 1.4:1. The most common symptom was fever (98%) and the most common physical finding was painless enlargement of lymph nodes (90%). There was statistically significant association between FNAC and definite diagnosis, diagnosis suspected and undiagnosed cases of tuberculosis by FNAC (Chi-square value=11.37, p<0.05), for Hodgkin’s lymphoma (Chi-square value=17.64, p<0.01). FNAC has significant association in detecting tuberculosis, Hodgkin’s, and non-Hodgkin’s diseases of childhood (p<0.05). Conclusion: FNAC can be used as a first-line diagnostic test for tuberculosis, Hodgkin’s disease, and non-Hodgkin’s lymphoma in the pediatrics age group in view of its availability.